Risk factors for failed fistula closure in Addis Ababa at fistula centre, central Ethiopia - Tadesse Mamo Dejene; Asrat Kassaw Belachew; Michael Amera Tizazu; Sadat Mohammed Yesuf (Frontiers Media S.A., 2024)
BackgroundObstetric Fistula leads to fecal and urine incontinence in women and girls. Surgical repair is the cornerstone of care. Failure to repair an obstetric fistula exposes women not only to repeated surgery but also to ongoing incontinence and its sequela, depression, and social exclusion. Which impacts the nation's health intervention programs and socioeconomic burden.ObjectiveTo determine factors associated with failed fistula closure in women who underwent Fistula Closure at the Hamlin Fistula Center in Addis Ababa, central Ethiopia, between February 10, 2018, and December 28, 2020.MethodsWomen who underwent Fistula Closure between February 10, 2018, and December 28, 2020 were included in a case-control study that was conducted between May and June 2021. In total, 417 study participants (139 cases and 280 controls) were selected using a systematic random sampling technique. Two professional midwife data collectors and one BSC nurse for the supervisory assessment of women's medical cards utilized a structured questionnaire to collect data. SPSS version 25 was used to enter, clean, and analyze the data. During data analysis, bivariate and multivariate regression models were used. A p-value of less than 0.05 indicates a significant correlation.ResultsForty-nine patients (35.3%) and 133 controls (47.8%) who were older than 26 years were at repair while they were (14-19 years old). The factors that contributed to failure of fistula closure included age at repair (14-19 years old) [AOR = 2.1, 95% CI (0.94-4.89)], prior fistula attempts (9.6, rural residence [AOR = 2.69, 95% CI (1.36-5.35)], height <150 cm [AOR = 1.80, 95% CI (0.99-3.59)], labor duration longer than 2 days [AOR = 1.89, 95% CI (0.99-3.59)], delivery by cesarean section [AOR = 1.88, 95% CI (1.04-3.89)], damaged urethra [AOR = 2.02, 95% CI (1.04-3.89)], diameter of fistula >3 cm, mild vaginal scar [AOR = 3.20, 95% CI (1.24-8.29)], moderate and severe vaginal scar [AOR = 5.49, 95% CI (1.92-15.75)], and completion of ANC [AOR = 0.20 (0.11, 0.38)].Conclusion and recommendationAge at the time of repair, Residence, Height, duration of labor, mode of delivery, completion of ANC, damaged urethra, fistula diameter >3 cm, previous fistula attempts, and vaginal scar are factors related to failure of fistula closure. By focusing on these areas, we can significantly improve the outcomes for patients undergoing fistula repair and lower the likelihood of failed closures in the future. Community-based health education regarding obstetric fistula and the importance of seeing a doctor as soon as possible during labor to lower the risk of obstructed delivery, boost antenatal care completion, and shorten the length of labor are all necessary to prevent failed fistula closure in comparable patients in the future.